An introduction to access security in UMTS. - Koien, G.M (IEEE Wireless communications)
The first generation of cellular mobile communications systems contained few if any security measures to protect the system operator and users. The second generation generally did a lot better, and contained entity authentication and confidentiality protection. Although this was a major improvement, security protection in the second generation left a lot to be desired. With the advent of 3G mobile systems a serious effort has been made to create a consistent security architecture based on the threats and risks a 3G system faces.